A longitudinal study of the differential social‐cognitive foundations of early prosocial behaviors. (17th December 2020) - Stout, Wyntre; Karahuta, Erin; Laible, Deborah; Brandone, Amanda C.
Abstract: A growing body of work has documented the emergence of instrumental helping and sharing in the second year of life; however, less is known about mechanisms that underlie development and production of prosocial behavior. The current study took a longitudinal approach to explore whether the origins of prosocial behaviors can be traced back to foundational social‐cognitive capacities emerging in infancy. In a sample of 90 children, longitudinal relations were examined between intention understanding and joint attention measured in infancy (8–12 months) and later instrumental helping and sharing behavior assessed in the toddler years (18–25 months). We expected social‐cognitive capacities supporting infants' understanding of others to be positively related to their prosocial behaviors as toddlers. Measured variable path analyses revealed two distinct developmental pathways from infant social cognition to later prosocial behavior: 1) Instrumental helping in the toddler years was positively predicted by intention understanding in infancy; 2) sharing in the toddler years was positively predicted by infants' initiating joint attention. These results lend support to proposals on the multidimensional nature of early prosocial behavior and offer the first longitudinal evidence that the origins of toddlers' prosocial behavior can be traced to social‐cognitive capacities emerging in infancy.